A single exposure to brivaracetam or perampanel does not cause cell death in neonatal rats - Witherspoon, Eric; Zuczek, Nicholas; Williams, Gabrielle; Bernstein, Briana; Ghosh, Anjik; Culjat, Marko; Kaushal, Suhasini; Forcelli, Patrick A. (Frontiers in Pediatrics, 2024)
Exposure to a range of anti-seizure medications (ASMs) during early brain development adversely impacts neurodevelopmental outcomes in both animal models and in clinical studies. Many ASMs, including phenobarbital (first line for neonatal seizures), phenytoin, valproate, and benzodiazepines, are associated with acute neurotoxicity (cell death), impaired synaptic development, and long-term behavioral changes following gestational or neonatal exposure in animals. This is mirrored in clinical studies which show lasting neurodevelopmental deficits following early-life or gestational exposure to these drugs. Brivaracetam (BRV) and perampanel (PER) are two newer generation anti-seizure medications and are of interest based on their mechanisms of action (SV2A modulator, AMPA antagonist, respectively), as other drugs with these mechanisms of action do not trigger acute neurotoxicity. Both BRV and PER show anti-seizure efficacy in developing animals, but potential neurotoxicity of these is unexplored. To address this gap, we treated postnatal day (P)7 Sprague-Dawley rats with BRV (20, 40, 80 mg/kg) and PER (0.1, 0.9, 2.7 mg/kg), and assessed the induction of cell death across a range of vulnerable brain regions 24 hours after exposure. Across the cortical, subcortical, limbic, and basal ganglia regions, while VPA (positive control) triggered cell death, neither BRV nor PER did so.Our results suggest that BRV and PER may have a positive safety profile -at least with respect to acute induction of cell death -and therefore may offer a safer option for the treatment of early life seizures.